Table of Content - - (Journal of Curriculum and Teaching Methodology, 2024)
Table of Content: 1. A Proposed Training Program for Developing Technology Integration Skills in Basic Education for Social Studies Teachers in Sana’a City in Light of Their Training Needs Asst-Prof. Nabil Abdullah Qaid Al-Emad, Co-Prof. Abdussalam Mohammed Ahmed Al-Salahi, Co-Prof. Najat Hasan Hasan Al-Faqeeh 2. Achievement Motivation Levels and Their Relationship with Social Cohesion among Basketball Students at the College of Sports Sciences Ms. Lama Mamdouh Alkhraishah 3. The Effectiveness of Digital Storytelling at Increasing Learning Motivation in Early Childhood from the Female Teachers’ Point of View Ms. Haya Saud Alshahrani 4. The degree of public school teachers’ acceptance of using the blended learning approach in the first three basic grades in the Southern Badia Education Directorate Dr. Mahmoud Khalaf Al-Mashaqba 5. The level of awareness of elements of national heritage among intermediate school students in the city of Abha Mr. Ali Essa Hadi Masmali, Prof. Mesfer Ahmad Mesfer Alwadai 6. The reality of teaching the digital skills course in the primary school: challenges and solutions in light of digital transformation Dr. Mohamed Saeed Alhabish, Mr. Ahmed Mohsen Alqarni, Mr. Ali Mohammed Alqarni , Mr. Abdulrahman Mohammed Alghamdi, Mr. Asim Homod Albarbi , Mr. Abdulkarim Saleh Almuntashiri 7. Special Education in the United States of America and the Potential for Benefit in the Kingdom of Saudi Arabia Ms. Nada Nasser Alqahtani